EVALUASI STATEGI DINAS PENDIDIKAN KABUPATEN KETAPANG DALAM PERCEPATAN PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA (Studi Kasus di SMP N 3 Kecamatan Hulu Sungai Kabupaten Ketapang) - Marsel Akin Elas E.01107092 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Based on Strategy of District Education Office 2011-2015  there was not program about increase of total number of teachers program . KnownfromtheOffice ofStrategystates thatyetunequal distribution ofthe number of teachersinKetapangDistrict, particularlyin remote areas.As seenonSMPN3Hulu Sungai thatincludes oneremote areainKetapangRegency. Thereforeit is necessary toevaluateaboutKetapangDistrict Education Office Strategy primarily concerned withincreasing the numberof teachersinthe programRemote Areas. In addition,Ketapang DistrictEducation Officeshould actfirmly againstthe teachersaccording to thewidely spreadinUrbantoready to serve theneeds ofthe community, especiallyin Remote Areas. Therebyacceleratingandequity of educationinKetapang Districtis expected torun in accordancewith the visionandmissionthathas beendetermined. Writing of this researchto illustrateof EvaluationStrategyKetapang DistrictEducation Officein the Development ofEducation inSecondarySchool Level, particularlyin Remote Areassuch asSMPN3Hulu Sungai ketapang.Key Word: Evalution, Strategy,  and Program